Limping But Blessed : Wrestling with God after the Death of a Child - Jones, Jason (Businessman) (Book collections on Project MUSE., 2017)
After the unexpected, accidental death of his three-year-old son, Jason Jones went on a long, painful journey to make sense of how God could have let this happen to his son and best friend, Jacob, and to their family. And he struggled intensely with his faith after everything he thought about God disintegrated on June 12, 2011. In Limping But Blessed, Jones explores struggling with faith and belief, dealing with his depression and grief, and searching for hope in a hopeless situation. The book includes tales of his darkest days, correspondence he had with Christian theologians, and what he's done to preserve his son's legacy. At some point in each of our lives, something goes terribly wrong, and our faith is shaken to the core. This book is the story of one man's journey through the darkest time of life searching for answers and a grueling attempt to find a sliver of hope to keep holding on.